Pengaruh Status Sosial Ekonomi Orang Tua Terhadap Minat Berwirausaha Alumni - Sri Nindra Mohulaingo; Radia Hafid; Agil Bahsoan; Rosman Ilato; Melizubaida Mahmud (State University of Gorontalo, 2023)
This study uses a quantitative approach. Data collection method used in this study consist of observation, interviews, documentation, and questionnaires. The research populations are 2019 and 2020 alumni of SMA Negeri Posigadan amounted to 107, while the samples are 52 alumni. This study uses simple linear regression analysis. The results show that parents’ socio-economic status has a positive and significant influence on entrepreneurial interenst of the 2019 and 2020 alumni of SMA Negeri Posigadan, Tomini Sub-district, Bolaang Mongondow Selatan Regency. Based on the research result, the coefficient of determination shows an R Square of 0,616, which means that 61,6% of the variability regarding the entrepreneurial interest of the 2019 and 2020 alumni of SMA Negeri Posigadan, Tomini Sub-district, bolaang Mongondow Selatan Regency is influenced by parents’ socio-economic status, while other variables influence the remaining 38,4%.